QTL Mapping for Phosphorus Efficiency and Morphological Traits at Seedling and Maturity Stages in Wheat - Yuan, Yuanyuan; Gao, Minggang; Zhang, Mingxia; Zheng, Honghua; Zhou, Xiuwen; Guo, Ying; Zhao, Yan; Kong, Fangmei; Li, Sishen (Frontiers in Plant Science, 2017)
Phosphorus (P) efficiency (PE), which comprises phosphorus uptake (PupE) and utilization efficiency (PutE), is considered as one of the most important factors for crop yield. In the present study, 11 seedling traits and 13 maturity traits related to wheat PE and morphology were investigated using a set of recombinant inbred lines (RILs) derived from the cross of “TN 18 × LM 6”, under hydroponic culture trials and field trials at low P (LP) and normal P (NP) levels in two different years, respectively. The LP input reduced of biomass, yield and PupE traits, but increased PutE traits. A total of 163 QTLs for seedling and maturity traits under different P levels and their AV, and 15 QTLs for relative traits were detected on 21 chromosomes. Of these, 49 and 63 QTLs for were detected specially in LP and NP treatments, respectively. We found 11 relatively high-frequency QTLs (RHF-QTLs) and four important QTL clusters, which may be the potential targets for marker-assisted selection (MAS) in wheat breeding programs for PE. Favorable relationships for breeding programs were found in the four important QTL clusters, which allow the possibility of improving the morphological traits and PutE simultaneously. A total of 29 markers which associated with 51 QTLs were found highly homologous with EST sequences, which suggested that they were potential functional loci. We suggested that the four biomass traits (SDW, RDW, TDW and RSDW), five yield traits (SN, PH, TGW, GWP and StWP) and two relative traits (Rstwp and Rgwp) can be considered as the primary indexes for the evaluation of PE for they are easy to identify on a large-scale.